AGARWOOD PRODUCING FUNGAL INOCULANT FORMULATION IN KETIMUNAN TREE (Gyrinops versteegii DOMKE) - Mega, I Made; Suanda, Dewa Ketut; Kasniari, Desak Nyoman; Susrama, I Gede Ketut (International Journal of Biosciences and Biotechnology; Vol 3 No 1 (2015))
This study aimed to find out the agarwood producing fungal inoculant formulation that infect Ketimunan tree (Gyrinops versteegii DOMKE) effectively and resulted in high quality of agarwood. Randomized Completely Block Design was applied in this study with formulation of Fusarium solani and Rhizopus sp inoculant in liquid and solid form were combined as treatments. Treatments were: solid Fusarium solani inoculant, solid Rhizopus sp inoculant, mixture of solid Fusarium solani inoculant and solid Rhizopus sp inoculant, liquid Fusarium solani inoculant, liquid Rhizopus sp inoculant, mixture of liquid Fusarium solani inoculant and liquid Rhizopus sp inoculant, and mixture of solid and liquid of Fusarium solani and Rhizopus sp inoculants. There are three replicates for each treatment. Parameters measured were level of fragrance, agarwood color, and its resin content. The result showed that all formulations affected resin content significantly compared to control of agarwood. Mixture of liquid Fusarium solani and liquid Rhizopus sp inoculant showed the best quality agarwood with quality characteristics: brownish black or agarwood with black and brownish black color, very strong fragrance, and with 13.58% resin content.
Keywords: agarwood forming fungi, Gyrinops versteegii